PHARMACOECONOMIC ASSESSMENT OF USING INTERFERON-FREE REGIMENS FOR CHRONIC HEPATITIS C AFTER LIVER TRANSPLANTATION - A. A. Sukhoruk; E. V. Esaulenko (Вестник трансплантологии и искусственных органов, 2016)
This article contains analysis of current combination treatment regimens for chronic hepatitis C after liver transplantation. Antiviral therapy with long-acting interferons and ribavirin is of low efficiency and high costs. The clinical and economic benefits of interferon-free treatment regimen for patients infected with genotype 1 HCV using dasabuvir, paritaprevir boosted with ritonavir, ombitasvir (Viekira Pak) and ribavirin have been shown. Registration and introduction into clinical practice of new direct-acting antiviral drugs will significantly expand the arsenal of tools for the treatment of recurrent HCV infections, in particular in patients infected with hepatitis C virus genotypes 2 and 3.